2000
DOI: 10.1034/j.1399-3003.2000.16d11.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough and gastro-oesophageal reflux: a double-blind placebo-controlled study with omeprazole

Abstract: Gastro-oesophageal reflux (GOR) is an important cause of chronic cough. There has been a lack of placebo-controlled trials treating GOR related chronic cough with antireflux therapy. The aim of this study was to determine the efficacy of omeprazole on GOR related chronic cough.After excluding other common causes of cough, oesophageal pH monitoring was performed on 48 patients with chronic cough. Twenty-nine patients found to have GOR were randomized in a double-blind fashion to receive omeprazole 40 mg o.d. or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 24 publications
5
105
0
7
Order By: Relevance
“…In a recent 5-year follow-up of the original ProGERD study, the prevalence of asthma in GERD patients had increased from 4.5% at entry to 7.8% at the end of follow-up. 82 Kiljander et al 83 showed that 35% of asthma patients had abnormal 24-hour esophageal pH monitoring.…”
Section: -74mentioning
confidence: 99%
“…In a recent 5-year follow-up of the original ProGERD study, the prevalence of asthma in GERD patients had increased from 4.5% at entry to 7.8% at the end of follow-up. 82 Kiljander et al 83 showed that 35% of asthma patients had abnormal 24-hour esophageal pH monitoring.…”
Section: -74mentioning
confidence: 99%
“…16,[34][35][36][37][38] Shaheen et al 37 ( Table 1 ) reported data separately for patients with and without pathologic esophageal acid exposure and, thus, contributed two datasets, resulting in a total of seven datasets for further analysis. One dataset showed no therapeutic gain ( Table 1 ).…”
Section: Therapeutic Response Of Chronic Cough To Acid-suppressive Thmentioning
confidence: 99%
“…Five used patient diaries consisting of visual analog scales to assess cough severity and/or frequency ( Table 1), 13,16,34,36,38 questionnaires were used in two studies ( Table 1 ), 14,35 and two studies did not specify the method of data acquisition ( Table 1 ). 15,37 Two studies assessed efficacy in terms of the proportion of patients who met prespecifi ed criteria for response ( Table 1 ) 16,36 ; the remainder measured change in mean cough scores relative to baseline for treatment vs placebo.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] On the contrary, other studies have shown a less good response rate. [33;34] In many of these studies, patients were asked to fill in a questionnaire about their symptoms, without using objective measurement for cough.…”
Section: Treatment Of Reflux Related Coughmentioning
confidence: 99%